A rare case of unruptured rudimentary horn pregnancy - GS, Triveni; Pandey, Nihita; Lal, Prabha; Singh, Abha (Indian Journal of Case Reports, 2019)
Mullerian anomalies are a rare disorder and pregnancy in a rudimentary horn is one of the rarest forms of an ectopic pregnancy. This rarity proves to be an obstacle in the timely diagnosis and management of such cases. Thereby, it often culminates in catastrophic events such as rupture of the rudimentary horn which can claim the life of the mother. In this case report, we study the presentation of a 27-year-old primigravida who was presented at 16 weeks gestation, with an intrauterine fetal demise and failed induction of labor. This case report highlights how the diagnosis of a rudimentary horn pregnancy is often missed and the pregnancy was prolonged. We also aim to emphasize the importance of keeping the possibility of a rudimentary horn pregnancy in mind while dealing with the failure of second-trimester pregnancy termination.